1995
DOI: 10.1177/001979399504800206
|View full text |Cite
|
Sign up to set email alerts
|

Is Job Stability Declining in the U.S. Economy?

Abstract: Using Current Population Survey data, the authors examine changes in job stability during the 1980s. For consecutive four-year periods during 1979–91, they present estimates of four-year retention rates for workers with varying levels of employer-specific seniority. Retention rates of low-seniority workers rose between 1979–83 and 1983–87 but fell between 1983–87 and 1987–91. Retention rates for 1987–91 were typically lower than those for 1979–83, suggesting a secular decline in job stability during the 1980s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 4 publications
0
47
0
Order By: Relevance
“…2 In an analysis of current population statistics (CPS) tenure supplements for , 1987, Diebold, Neumark, and Polsky (1994 showed that there was a decline in the retention rates of black relative to white workers, whereas all other subgroups experienced no such declines. According to Swinnerton and Wial (1995), retention, as a function of tenure, has an inverted-U shape for both black and white workers and for workers in nonprofessional services, a category that includes the entertainment industry. Their study covers the 1979-1991 period and uses the CPS tenure supplements from 1979, 1981, 1983, 1987, and 1991.…”
Section: Introductionmentioning
confidence: 99%
“…2 In an analysis of current population statistics (CPS) tenure supplements for , 1987, Diebold, Neumark, and Polsky (1994 showed that there was a decline in the retention rates of black relative to white workers, whereas all other subgroups experienced no such declines. According to Swinnerton and Wial (1995), retention, as a function of tenure, has an inverted-U shape for both black and white workers and for workers in nonprofessional services, a category that includes the entertainment industry. Their study covers the 1979-1991 period and uses the CPS tenure supplements from 1979, 1981, 1983, 1987, and 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Recent anecdotal evidence from academic treatises and media accounts indicate that, with regard to layoffs, which are typically based on the discretionary judgment of employers (Cornfield, 1983;McCune et al, 1988), African Americans "do not have opportunities to demonstrate their value to employers" (McCune et al, 1988:148) and have to work "twice as hard" to avoid "getting the axe" (Zwerling and Silver, 1992:655). If accurate, these statements indicate that African Americans are relatively susceptible to "negative stratificationbased events" (Featherman and Hauser, 1978) which, even if temporary, have long-lasting consequences, such as delaying the timing (Fairlie and Kletzer, 1998;Leana and Feldman, 1995;Root, 1988) and reducing the level of socioeconomic rewards over the career (Golden, 1992;Mouw, 2000;Swinnerton and Wial, 1995).…”
mentioning
confidence: 99%
“…The issue of job stability perhaps first gained notoriety among industrial and labor relations scholars concerned about the apparent structural displacement of workers in the U.S. economy during the 1970s and 1980s (Carter 1988;Hall 1982;Osterman 1988;Swinnerton and Wial 1995;Ureta 1992). Perhaps using Japan as a model, Weitzman (1984) hypothesized that "share economies," in which most firms pay a significant proportion of worker compensation based on firm performance (i.e., profit sharing), would experience lower rates of unemployment and lower variability of aggregate levels of employment.…”
Section: Employment Stabilitymentioning
confidence: 99%